Whole exome sequencing make a definitive diagnosis of a Vietnamese patient with a late onset urea cycle disorder - Nguyen, Ngoc-Lan; Nguyen, Ngoc Khanh; Vu, Chi Dung; Thu Huong, Nguyen Thi; Huy Hoang, Nguyen (Vietnam Journal of Biotechnology, 2020)
Our report describes a female presenting with vomiting, fever, coma and right hemiplegia at 26 months of age. Biochemical tests revealed hyperammonemia, hyperlactatemia, elevated glutamine level, elevated transaminase and disorder of prothrombin time. She was priory diagnosed with urea cycle disorders (UCDs). UCDs are caused by mutations in eight genes that regulate the synthesis of enzymes and cofactors involved in urea metabolism. Singleton whole exome sequencing was applied to screen causative variants in these genes in the patient at 6 years of age. The result showed one heterozygous stop loss mutation c.1065A>G in the OTC gene as a potential disease causing in the patient. The mutation c.1065A>G leads to alternation of stop codon to tryptophan, resulting in elongation of fourteen amino acids in ornithine transcarbamylase (OTC) protein (p.Ter355TrpextTer14). Sanger sequencing in the family revealed the mutation c.1065A>G was not present in healthy parents and brother. Therefore, this mutation is considered as a de novo mutation in the patient. The mutation c.1065A>G was conferred to pathogenic according to the standards and guidelines of the American College of Medical Genetics and Genomics and the Association for Molecular Pathology with 1 strong (PS2), 3 moderate (PM2, PM4 and PM5) and 1 support criteria (PP2). Although OTC deficiency is an X-linked recessive inheritance, approximately 15% of females carrying heterozygous variants showed the late onset OTC deficiency. Therefore, in combination of clinical presentations, laboratory findings and molecular genetic analyses, we made a definitive diagnosis of the patient with late onset OTC deficiency, a disorder of UCDs.